2.1 THE RELATIVE IMPORTANCE OF CENTRAL AND BRACHIAL BLOOD PRESSURE IN PREDICTING CARDIOVASCULAR EVENTS: AN INDIVIDUAL PARTICIPANT META-ANALYSIS OF PROSPECTIVE OBSERVATIONAL DATA FROM 22,433 SUBJECTS - McEniery, Carmel; Ben-Shlomo, Yoav; May, Margaret; Spears, Melissa; Brumback, Lyndia; Cameron, James; Chen, Chen-Huan; Chirinos, Julio; Czarnecka, Danuta; Dart, Anthony; Devereux, Richard; Dhaun, Neeraj; et al. (Artery research, 2016)
Systolic blood pressure (SBP) differs between the brachial artery and aorta. Prospective data suggest that central pressure predicts future cardiovascular events, but it is unclear if it is superior to brachial pressure. Methods and Results: A systematic review and individual participant data meta-analysis from 15 studies was undertaken. Study-specific associations of central and brachial pressure with cardiovascular outcomes, with and without mutual adjustment, were determined using Cox proportional hazard models, and random effect models to estimate pooled estimates. Of 22,433 participants, 908 had a myocardial infarction (MI) and 641 a stroke. The pooled age, sex, height and heart rate adjusted hazard ratio (HR) [95% CI] per SD increase in brachial SBP was 1.17 [1.03, 1.32] for MI and 1.28 [1.13, 1.46] for stroke and 1.16 [1.02, 1.33] and 1.33 [1.15, 1.53] for central SBP, respectively. Mutual adjustment attenuated the HRs for MI: brachial SBP (1.16 [0.90, 1.48]), central SBP (1.09 [0.87, 1.38]) and stroke: brachial SBP (1.18 [0.97, 1.42]), central SBP (1.19 [0.99, 1.44]). However, associations between central SBP and stroke, after adjustment for brachial SBP, were higher in those aged <61 years than in older individuals (1.83 versus 1.08 p-interaction <0.001). Conclusion: Brachial and central SBP have similar associations with future CV events. Larger studies are required to test whether central SBP may be a more powerful predictor of stroke risk in younger individuals.